Ethical Issues in Infant Feeding After disasters - Binns, Colin; Lee, M.; Tang, Li; Yu, Chuan; Hokama, T.; Lee, Andy (Sage Science Press, 2012)
In the aftermath of many disasters the silence is punctuated by the crying of infants, hungry infants. The aim of this paper is to discuss ethical issues in feeding infants after disasters. The Asia Pacific region generates 25% of the world’s GDP, but experiences 45% of natural disasters and 42% of the economic losses due to disasters. The region has 61% of the world’s population, but 86% of the population affected by disasters. Breastfeeding, exclusive to six months and continuing thereafter, is important for growth and the health of the infant in the short term and later in life. In most natural disasters, mothers and infants will both suffer, but in some disasters, such as earthquakes and building collapses, infants can survive in small spaces. Infants separated from mothers require a wet nurse (rarely available) or feeding with infant formula and sterile water. Formula companies often donate supplies of infant formula but distribution should follow ethical principles. Mothers who are injured or short of food can still continue breastfeeding and don’t need formula. Where formula must be used, health workers need to follow the highest ethical standards to avoid promoting infant formula to vulnerable communities in the post recovery phase.